Active Ageing of Elderly People and Its Determinant: Empirical Evidence from Thailand - Chansarn, Supachet (Animo Repository, 2012)
This study aims to assess the active ageing of elderly people aged 60 to 95 years old in Thailand and to investigate its determinants based on the data obtained from the National Statistical Office’s elderly survey in 2007. The findings revealed that elderly people in Thailand had moderate active ageing. In terms of each dimension, this found that elderly people had high active ageing under the health dimension, moderate active ageing under the security dimension, and low active ageing under the participation dimension. Additionally, the regression analysis indicated that age and living in urban areas had negative impacts on the active ageing of elderly people, whereas physical exercise, alcohol consumption, receipt of useful information, awareness of social benefits for elderly people, education, and saving duration had positive influences on it. The active ageing of elderly people in Thailand was also determined by their most important sources of income. Moreover, the findings revealed that family warmth was positively related to the active ageing of elderly people in Thailand. That is, living with a spouse and children under 18 years old and receiving basic needs, visits, and telephone contacts from children helped promote the active ageing of Thai elderly people. However, living with grandchildren and receiving money from children less than 10,000 baht per year were found to have a negative relationship with the active ageing of elderly people.